Sleep Country Canada to provide the best night's sleep for athletes and officials at the 2010 Winter Games (SIRC Press Release, 2008)
When settling in for an important night's rest at the 2010 Winter Games, athletes and officials will enjoy the comfort and quality of a Sleep Country Canada bed.